1997
DOI: 10.1080/02688699746041
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar disc herniations in children: a long-term clinical and magnetic resonance imaging follow-up study

Abstract: To determine the long-term outcome of 12 youthful patients with lumbar disc herniation, who, at the time of surgery, were 15 years old and younger (mean age at operation 14.3 years), we assessed their current clinical condition (mean follow-up time 6 years) with a questionnaire inquiring about symptoms and disability, and radiologically with an MRI of the lumbar spine. Clinically, only five patients (40%) were totally asymptomatic and seven patients (60%) had recurring symptoms, both and disability. On MRI, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…The actual incidence of adolescent HIVD is difficult to establish due to the following reasons. First, published series adopted different ranges of age 4,7,10,11. When an upper limit of 15 years was adopted, an epidemiologic study, following 12058 Finnish babies from birth until 28 years of age, showed no prevalence of confirmed HIVD.…”
Section: Discussionmentioning
confidence: 99%
“…The actual incidence of adolescent HIVD is difficult to establish due to the following reasons. First, published series adopted different ranges of age 4,7,10,11. When an upper limit of 15 years was adopted, an epidemiologic study, following 12058 Finnish babies from birth until 28 years of age, showed no prevalence of confirmed HIVD.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence studies have reported that 0.5-6.8% of all patients hospitalized for LDH are pediatric cases 3 , 7 , 8 , 13 , 14 , 16 , 21 , 27 , 31) . However, the real prevalence of adolescent LDH is difficult to establish for various reasons, for example, the different age ranges adopted in published series 4 , 13 , 19 , 21) . A literature review revealed that one previous study addressed the prevalence of Korean adolescent LDH 14) .…”
Section: Discussionmentioning
confidence: 99%
“…Особенно актуален данный вопрос у детей и подростков, так как полное или максимальное удаление диска в данном случае считается неоправданным. Так, по данным Luukkonen et al [18], это может привести к повторному стенозу невральных структур в связи с резким снижением высоты диска и развитию дегенеративных изменений в смежных сегментах. Кроме того, по данным Ishihara et al [11].…”
Section: результаты и их обсуждениеunclassified